Franz Delitzsch (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Franz Delitzsch." Produced by: Photograph, artistilsche, Anstalt von August Brasch, Leipzig, Linden-Strasse No. 7. These dates are approximate.